Antimicrobial Activity of Calcium Hydroxide and Betamethasone on Enterococcus faecalis; An in vitro Assessment - Tabrizizadeh, Mahdi; Rasti, Mojtaba; Ayatollahi, Fatemeh; Mosadegh, Mohammad Hossein; Zandi, Hengameh; Dehghan, Farzad; Mousavi, Zohreh (Iranian Endodontic Journal, 2015)
Introduction: Calcium hydroxide (CH) is one of the most common intracanal medications. Corticosteroids (CS) are used in endodontics because of their anti-inflammatory activity. This study aimed to evaluate the antimicrobial effect of CH+betamethasone and CH+saline against Enterococcus faecalis (E. faecalis) using agar diffusion test and measuring the microbial zone of inhibition (ZOI). Methods and Materials: Four plates containing Mueller-Hinton broth and E. faecalis culture media, were prepared. In each plate, 5 holes (5×3 mm) were created and a creamy mixture of CH+betamethasone was inserted into the holes (10 holes for each material). Two holes with ampicillin disks and two empty holes were used as negative and positive controls, respectively. Plates were incubated for 24 h and then the diameter of microbial ZOI was measured. The pH of each mixture was measured by pH meter. Data were analyzed using the Mann-Whitney U test. Results: The mean diameter of ZOI for CH+betamethasone and CH+saline was 3.4 and 3 mm, respectively. The difference was not significant (P=0.143). The pH was 12.5 for CH+saline and 12.3 CH+betamethasone, respectively. Conclusion: The mixture of CH+betamethasone had good antimicrobial effects against E. faecalis. Further studies are needed to confirm the value of this mixture in clinical settings. Keywords: Antimicrobial Activity; Betamethasone; Calcium Hydroxide; Enterococcus faecalis; Intracanal Medication